BONDING CHARACTER OF SIO2 STISHOVITE UNDER HIGH PRESSURES UP TO 30 GPA - Yamanaka T.; Fukuda T.; Mimaki J. (My University, 2002)
The charge density and bond character of the rutile-type structure of SiO2 (stishovite) under compression to 30 GPa were investigated by X-ray diffraction study using synchrotron radiation and AgKα rotating anode X-ray generator through a newly devised diamond-anvil cell. The valence electron density was determined by least-squares refinement including the κ parameter and the electron population in the X-ray atomic scattering parameters. The oxygen κ-parameter of SiO2 is 0.94 under ambient conditions and 1.11 at 29.1 GPa and the silicon valence changes from +2.12(8) at ambient pressure to +2.26(15) at 29.1 GPa. These values indicate that the electron distributions are more localized with increasing pressure. The difference Fourier map shows the deformation of the valence electron distribution and the bonding electron population in residual electron densities. The bonding electron observed from the X-ray diffraction study is interpreted by molecular orbital calculations. The deformation of SiO6octahedra and the bonding electron density of stishovite structures are elucidated from the overlapping electron orbits. The O-O distances of shared and unshared edge of SiO6 octahedra change with the cation ionicity. The repulsive force between the two cations in the adjacent octahedron makes its shared edge shorter. The pressure changes of the apical and equatorial Si-O interatomic distances are explained by the electron density of state (DOS) of Si and electron configuration.
Keywords: SIO2STISHOVITE STRUCTURE; SYNCHROTRON RADIATION; HIGH PRESSURE UP TO 30 GPA; VALENCE ELECTRON POPULATION; SI-O BOND CHARACTER UNDER COMPRESSION